2019
DOI: 10.1038/s41467-019-11558-2
|View full text |Cite|
|
Sign up to set email alerts
|

A meta-analysis of genome-wide association studies identifies multiple longevity genes

Abstract: Human longevity is heritable, but genome-wide association (GWA) studies have had limited success. Here, we perform two meta-analyses of GWA studies of a rigorous longevity phenotype definition including 11,262/3484 cases surviving at or beyond the age corresponding to the 90th/99th survival percentile, respectively, and 25,483 controls whose age at death or at last contact was at or below the age corresponding to the 60th survival percentile. Consistent with previous reports, rs429358 (apolipoprotein E (ApoE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
301
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(328 citation statements)
references
References 61 publications
8
301
0
2
Order By: Relevance
“…First, the variant has not been implicated in any of the largescale genome-wide association studies on mortality or parental life span that have been performed in recent years. (9) Second, if the M variant confers an increased mortality rate, one might expect it to be relatively depleted in older individuals, in turn causing frequencies of II, IM, and MM genotypes to diverge from those expected (i.e., violation of Hardy-Weinberg equilibrium). PNPLA3 p.I148M genotypes have been in Hardy-Weinberg equilibrium in several large cohorts, (10) again arguing against an effect on mortality.…”
Section: Pnpla3 I148mmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the variant has not been implicated in any of the largescale genome-wide association studies on mortality or parental life span that have been performed in recent years. (9) Second, if the M variant confers an increased mortality rate, one might expect it to be relatively depleted in older individuals, in turn causing frequencies of II, IM, and MM genotypes to diverge from those expected (i.e., violation of Hardy-Weinberg equilibrium). PNPLA3 p.I148M genotypes have been in Hardy-Weinberg equilibrium in several large cohorts, (10) again arguing against an effect on mortality.…”
Section: Pnpla3 I148mmentioning
confidence: 99%
“…Why is it surprising that PNPLA3 p.I148M associates with increased all‐cause mortality? First, the variant has not been implicated in any of the large‐scale genome‐wide association studies on mortality or parental life span that have been performed in recent years . Second, if the M variant confers an increased mortality rate, one might expect it to be relatively depleted in older individuals, in turn causing frequencies of II, IM, and MM genotypes to diverge from those expected (i.e., violation of Hardy‐Weinberg equilibrium).…”
mentioning
confidence: 99%
“…While the association between ApoE and recent arrival seems to be at odds with the higher level of ApoE expression by female peritoneal macrophages, ApoE expression may also be controlled partly by estrogen, as the Apoe gene contains an estrogen response element, and its expression is reduced in inflammatory peritoneal macrophages by macrophage-specific deletion of the estrogen receptor alpha 35 . Understanding how ApoE expression is regulated by tissue-residency and hormonal control may be important in many diseases in which is it is a known genetic risk factor and that exhibit strong sex-biases in risk, such as Alzheimer’s and cardiovascular disease 60 , but also in healthy aging where APOE variants are among the strongest predictors of human longevity 61 .…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the identified loci could not be replicated in independent studies as yet. In addition, the largest and most recent longevity GWAS, based on cases belonging to the top 10% oldest survivors, again only replicated association of the APOE locus 32 .…”
Section: Mainmentioning
confidence: 93%
“…In previous work, we showed that longevity defined as top 10% survivors or more extreme is transmitted to subsequent generations 16 . With this, a consistent definition of longevity was provided that is also adopted in the largest longevity GWAS up to now 32 . In addition, we showed that every additional long-lived relative independently contributes to the survival advantage of study participants, according to their genetic distance 16 .…”
Section: Mainmentioning
confidence: 99%